1984
DOI: 10.1007/bf00042845
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion problem in semiconductor technology

Abstract: This paper deals with a mathematical model of a SEM-EBIC experiment devised to measure the diffusion length of semiconductor materials. In the model the semiconductor material occupies a half-space, of which the plane bounding surface is partly covered by a semi-infinite current-collecting junction, the Schottky diode. A scanning electron microscope (SEM) is used to inject minority carriers into the material. It is assumed that injection occurs at a single point only. The injected minority carriers diffuse thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…As the beam is moved away from the barrier/junction in a line-scan mode, the current decays as fewer and fewer minority carriers are able to diffuse to the space-charge region. The mathematical model for EBICurrent [20], shows that the decay of current, I EBIC , can be described by the following expression:…”
Section: Electron Beam Induced Current Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…As the beam is moved away from the barrier/junction in a line-scan mode, the current decays as fewer and fewer minority carriers are able to diffuse to the space-charge region. The mathematical model for EBICurrent [20], shows that the decay of current, I EBIC , can be described by the following expression:…”
Section: Electron Beam Induced Current Techniquementioning
confidence: 99%
“…It should be noted that in Ref. [20], the authors analyzed only the two asymptotic cases, namely v s = 0 and v s = ∞, and found that  = -1/2 for the former and -3/2 for the latter. Later, Chan et.…”
Section: Electron Beam Induced Current Techniquementioning
confidence: 99%
“…Depending on the given problem, such boundary conditions may be defined in space or time, and may range over discrete or continuous independent variables. The Wiener-Hopf technique has found application in an very wide variety of research areas, including the diffraction of acoustic, elastic and electromagnetic waves, crystal growth [60], fracture mechanics, flow problems [61], diffusion models [62], geophysical applications [63] and mathematical finance. A simple search of the science literature will reveal the many thousands of articles that have employed Wiener and Hopf's elegant method.…”
Section: Wiener-hopf Special Issuementioning
confidence: 99%
“…The infinite summation in (16) was approximated by using 400 terms. For the L-shaped geometry, the investigated parameters were the junction depth h, the diffusion length L, and the depth of the generation source z.…”
Section: Computation and Simulationmentioning
confidence: 99%
“…Donolato, on the other hand, derived the expression for the case of zero surface recombination velocity [15]. The expression for any value of surface recombination velocity was derived by Boersma et al [16]. This expression was used in the analysis and development of measurement techniques for the planarcollector configuration [17], [18].…”
Section: Introductionmentioning
confidence: 99%